2018
DOI: 10.1088/1555-6611/aaa115
|View full text |Cite
|
Sign up to set email alerts
|

Self-compression of spatially limited laser pulses in a system of coupled light-guides

Abstract: The self-action features of wave packets propagating in a two-dimensional system of equidistantly arranged fibers are studied analytically and numerically on the basis of the discrete nonlinear Schrödinger equation. Self-consistent equations for the characteristic scales of a Gaussian wave packet are derived on the basis of the variational approach, which are proved numerically for powers P < 10Pcr exceeding slightly the critical one for self-focusing. At higher powers, the wave beams become filamented, and th… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 56 publications
0
11
0
Order By: Relevance
“…Figure 1 shows schematically an MCF fiber with N = 3. The analysis will be based on the standard theoretical model [7,8,13,16,17,27,37], in the framework of which it is assumed that the fundamental guided modes of the optical cores oriented parallel to the z-axis are weakly coupled. In this case, the propagation of laser pulses in the MCF can be described approximately as a superposition of fundamental modes localized in each core (1) where φ(x, y) is the structure of the lowest spatial mode in the core, E n is the envelope of the electric field strength in the n-th core, which slowly changes along the z-axis.…”
Section: Formulation Of the Problemmentioning
confidence: 99%
See 2 more Smart Citations
“…Figure 1 shows schematically an MCF fiber with N = 3. The analysis will be based on the standard theoretical model [7,8,13,16,17,27,37], in the framework of which it is assumed that the fundamental guided modes of the optical cores oriented parallel to the z-axis are weakly coupled. In this case, the propagation of laser pulses in the MCF can be described approximately as a superposition of fundamental modes localized in each core (1) where φ(x, y) is the structure of the lowest spatial mode in the core, E n is the envelope of the electric field strength in the n-th core, which slowly changes along the z-axis.…”
Section: Formulation Of the Problemmentioning
confidence: 99%
“…Again, it is possible to show the uniqueness of the functional F (13) turning to zero only for the ±-mode with κ m = π (that is, m = N ). For all other m = N , functional (13) can be set to zero for u n = u (m) n . This fact reflects the presence of filamentation instability at κ m = π.…”
Section: Spatio-temporal Solitonmentioning
confidence: 99%
See 1 more Smart Citation
“…A number of interesting results have been obtained in such MCFs: supercontinuum generation [23][24][25], the laser pulse compression [24][25][26][27][28][29][30][31][32], nonlinear switching [33] and the light bullet formation [24][25][26][27][28][29][30][34][35][36][37]. However, most of them were obtained for in-phase field distributions, which are influenced by a discrete analogue of filamentation instability and stochasticity [38].…”
Section: Introductionmentioning
confidence: 99%
“…Studies have shown that self-focusing of wide wave field distribution with a power exceeding a certain critical value [24] (which differs from the critical self-focusing power in a homogeneous non-linear medium) leads to decomposition of the wave field into a set of incoherent structures [4] in the process of propagation in a medium with a periodic set of weakly coupled optical fibers. For stable operation with more powerful wave beams, one can use multi-core optical fibers (MCF) with a small number of cores.…”
Section: Introductionmentioning
confidence: 99%